PRECISION LIVESTOCK FARMING: INNOVATIONS IN FEED MANAGEMENT AND ANIMAL HEALTH FOR OPTIMIZED PRODUCTION EFFICIENCY - Williams, Sarah; Green, Jessica; Turner, Michael (Techno Agriculturae Studium of Research, 2026)
Precision Livestock Farming (PLF) has emerged as a strategic approach to address efficiency, sustainability, and animal welfare challenges in modern livestock systems. Advances in sensor technologies, data analytics, and automated decision-support tools have enabled real-time monitoring of feed intake, animal behavior, and health status, yet empirical evidence on their integrated impacts remains fragmented. This study aims to evaluate how innovations in precision feed management and animal health monitoring contribute to optimized production efficiency in intensive livestock systems. The research employed a quantitative experimental design combined with farm-level monitoring, involving sensor-based feed delivery systems, wearable health sensors, and automated data analytics across selected commercial livestock farms. Performance indicators included feed conversion ratio, growth or productivity rates, health incidence, and resource-use efficiency. The results demonstrate that precision-managed feeding significantly reduced feed waste while improving feed conversion efficiency, whereas continuous health monitoring enabled early disease detection and reduced morbidity rates. Integrated PLF systems produced measurable gains in overall productivity and operational efficiency compared to conventional management practices. The study concludes that the synergistic application of precision feed management and animal health technologies enhances production efficiency while supporting animal welfare and resource sustainability. These findings highlight the potential of PLF as a transformative pathway for resilient and data-driven livestock production systems.